Development of high thermal conductivity of Ag/diamond composite sintering paste and its thermal shock reliability evaluation in SiC power modules - Yuxin Xu; Xiaoming Qiu; Wangyun Li; Suyu Wang; Ninshu Ma; Minoru Ueshima; Chuantong Chen; Katsuaki Suganuma (Journal of Materials Research and Technology, 2023)
Diamond has the highest thermal conductivity among naturally occurring materials and a relatively low coefficient of thermal expansion (CTE), making it a promising interconnected material for next-generation semiconductor power devices. In this study, Ag/diamond composite sintering paste was developed. The agglomerated diamond particles were uniformly dispersed in the sintered Ag porous structure, and the thermal conductivity was increased from 171.4 W/(m·k) for pure Ag sintering to 288 W/(m·k) for an Ag@2%diamond (2% of the total weight of Ag) specimen. The interfacial microstructure evolution and fracture behavior were investigated in detail for a SiC/Direct Bond Copper (DBC) joint structure during an extreme thermal shock test (TST) in the range of −50 °C–250 °C. Importantly, with a moderate amount of diamond additive, the microstructural degradation and severe deformation of the DBC substrate were effectively suppressed. This is mainly attributed to the diamond addition, which can block the migration pathways of Ag atoms toward long-term thermal shock and adjust the thermo-mechanical performance of the sintered layer. This detailed study about Ag/diamond composite paste can provide new guidance for strengthening sintered Ag interconnections for SiC power modules.